Ventricular tachycardia and myocardial infarction during antiarrhythmic therapy: a case report - A. A. Gurbanova; K. G. Pereverzeva; S. S. Yakushin; I. V. Budanova (Рациональная фармакотерапия в кардиологии)
The article analyzes the case of the development of ventricular tachycardia and type 2 myocardial infarction (MI) in an 80-year-old patient with a history of coronary artery disease, MI and chronic heart failure. In 2020, the patient was diagnosed with ventricular extrasystole and started antiarrhythmic therapy with diethylamino propionylethoxycarbonylaminophenothiazine 150 mg per day and sotalol 160 mg per day. In 2022, the patient had an episode of clinical death due to ventricular tachycardia with successful resuscitation. A diagnosis of non-ST-elevation acute coronary syndrome was made, coronary angiography was performed, which did not reveal significant coronary stenosis. Upon further examination, the dynamics of biomarkers of myocardial necrosis confirmed the diagnosis of acute MI. In the analyzed case, the development of ventricular tachycardia and MI is most likely associated with the intake of diethylaminopropionylethoxycarbonylaminophenothiazine in combination with sotalol, prescribed in the presence of contraindications to their use.